b-1=-9

Simple and best practice solution for b-1=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-1=-9 equation:


Simplifying
b + -1 = -9

Reorder the terms:
-1 + b = -9

Solving
-1 + b = -9

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + b = -9 + 1

Combine like terms: -1 + 1 = 0
0 + b = -9 + 1
b = -9 + 1

Combine like terms: -9 + 1 = -8
b = -8

Simplifying
b = -8

See similar equations:

| 180=115+x+x | | X-3/5x | | 2x+8+6x-4=84 | | 7=3y-17 | | 6x-(4x-32)=0 | | 125m-100m+43,650=45,675-300m | | (16x-3)(4)=0x | | 4(6p-3)=-39-3p | | -.4*p+2=.2*p+11 | | (16x-3)(4)=0 | | 10x-6=7x | | y+(-10)=36 | | 8y+1=2y-26 | | .5f+10=48 | | 6(2x+3)+2= | | (16x-3)(2)=0 | | 8p+9p=34 | | a-6-7a=1-6a | | 11c-4-3=8 | | (16x-3)(8)=0 | | 1/3x-1/6y=1 | | -4/5a=12/17 | | 2x-6=8-2x | | 3=2y | | 16x+3=47 | | 4+17/-2=0 | | 8(2a-8)=-4(-3a+6) | | 2c+c+12=14 | | 1/2f+10=48 | | 33/d=12 | | z/14=-28 | | 1-2x=-9+8x |

Equations solver categories